Academic Writing at the Graduate Level: Improving the Curriculum through Faculty Collaboration - Bair, Mary; Mader, Cynthia (Journal of University Teaching and Learning Practice, 2013)
This article describes a collaborative self-study undertaken to identify the source of academic writing difficulties among graduate students and find ways to address them. Ten faculty members in a college of education came together to define the problem and to analyze data gleaned from faculty and student surveys, course documents, course assignments, and course assessments. We found discrepancies between faculty and student perceptions about graduate preparation for academic writing and between the espoused and enacted curriculum. Both faculty and students identified problems associated with synthesizing theory and research. We discuss the need for teacher-scholars in today's educational environment, the challenges facing curriculum improvement, and several program-specific measures being undertaken to address identified gaps in academic writing and critical thinking.